Answer:
[tex]y=2x-5[/tex]
Step-by-step explanation:
You may replace the [tex]x[/tex] with [tex]c[/tex] according to your question's requirement.
We can use the point slope form to find the equation of a straight line.
[tex](y-{y__1}})=m(x-{x__1})[/tex]
But first, let's find the slope [tex]m[/tex] between the two points.
[tex]m = \frac{-3-(-7)}{1-(-1)} = \frac{4}{2} = 2[/tex]
Then, let's use the point [tex](1,-3)[/tex] and plug them into [tex]x__1[/tex] and [tex]y__1[/tex]
[tex](y-{{-3)}})=2(x-{1})[/tex]
Equation: [tex]y = 2x - 5[/tex] (or [tex]y = 2c - 5[/tex] in your case)